Challenges for palliative care in times of COVID-19: a scoping review protocol (Research, Society and Development, 2023)
Introduction: The COVID-19 Pandemic had a major impact on health personnel, families and the person receiving palliative and end-of-life care. Global measures to reduce contamination have forced a change in the practice. The fear of getting infected, restricted visits and the use of personal protective equipment challenged communication between the multidisciplinary team and the person and family in palliative and end-of-life care. The suffering of an end-of-life experience was compounded by long periods of loneliness. Synthesizing evidence from these experiences can inform decision-making and health policy for future global pandemics. Objectives: To map the experience of health personnel, the person and the family in palliative and end-of-life care, during the COVID-19 pandemic. Methods: This scope review will follow the JBI methodology for scoping reviews. Two independent reviewers will evaluate the articles and extract and synthesize the data. It will include studies published in Spanish, English and Portuguese, since March 2020. The following electronic databases will be searched: CINAHL Complete, MEDLINE, Scopus, SciELO, Psychology and Behavioral Sciences, MEDIClatina Cochrane Central Register of Controlled Trials and Access Scientific Repository, opened in Portugal. Results: This scoping review is expected to include studies that address the experience of health personnel, the person and the family in the context of palliative and end-of-life care during the COVID-19 pandemic. Conclusion: This scoping review will analyze and synthesize the available scientific evidence on the experiences of health personnel with people and families in palliative care during COVID-19. It can also be the basis for a systematic review and/or help identify gaps where it may be important to invest in the future. The protocol for this revision is registered with OSF under number OSFHOME-z6agy-v1.